PENGUJIAN DAYA PANCAR ANTENA YAGI TERHADAP EMPAT JENIS ANTENA PENERIMA - Andy Sri Irtawaty; Maria Ulfah; Hadiyanto Hadiyanto (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2017)
In this study, yagi antena is used as a receiving antena at a frequency of 500 MHz. The receiving antena to be tested for its characteristics are 4 types, namely dipole antena, monopole antena, circular loop antena and yagi antena. The purpose of this research is to know the quality of antena yagi as the sending antena to 4 types of receiving antena tested. The parameters used as benchmark comparison is the gain and antena polarization. The process of measuring the parameters of antena yagi as transmitter antena and dipole antena, monopole antena, circular loop antena and yagi antena as the receiving antena is done by an antena trainner with supporting software. Data retrieval is done in 2 conditions namely Line Of Sight (LOS) and using obstacle (NO-LOSS). The distance between the transmitting antena and the receiving antena is 1.5 meters, 2 meters, 2.5 meters, 3 meters and 5 meters. The slope position of the antena is also a determining factor in the measurement process. There are 3 categories namely, horizontal (antena sender) and horizontal (antena receiver), vertikal (antena sender) and vertikal (antena receiver) and combination of horizontal (antena sender) and vertikal (antena receiver).. The results of antena quality testing showed that among the 4 types of antena (dipole, monopole, circular loop and yagi), it was proven that the yagi antena had a perfect 100% accuracy test. The yagi antena is proved to have a gain value and an ideal radiation pattern, so it is suitable to be implemented as a transmitting antena and receiving antena.